Persistent varicella zoster virus infection following mRNA COVID‐19 vaccination was associated with the presence of encoded spike protein in the lesion - Mayuko Yamamoto; Misaki Kase; Hozumi Sano; Reiko Kamijima; Shigetoshi Sano (Journal of Cutaneous Immunology and Allergy, 2023)
Abstract Background Since the campaign of vaccination against COVID‐19 was started, a wide variety of cutaneous adverse effects after vaccination has been documented worldwide. Varicella zoster virus (VZV) reactivation was reportedly the most frequent cutaneous reaction in men after administration of mRNA COVID‐19 vaccines, especially BNT162b2. Aims A patient, who had persistent skin lesions after BNT162b2 vaccination for such a long duration over 3 months, was investigated for VZV virus and any involvement of vaccine‐derived spike protein. Materials & Methods Immunohistochemistry for detection of VZV virus and the spike protein encoded by mRNA COVID‐19 vaccine. PCR analysis for VZV virus. Results The diagnosis of VZV infection was made for these lesions using PCR analyses and immunohistochemistry. Strikingly, the vaccine‐encoded spike protein of the COVID‐19 virus was expressed in the vesicular keratinocytes and endothelial cells in the dermis. Discussion mRNA COVID‐19 vaccination might induce persistent VZV reactivation through perturbing the immune system, although it remained elusive whether the expressed spike protein played a pathogenic role. Conclusion We presented a case of persistent VZV infection following mRNA COVID‐19 vaccination and the presence of spike protein in the affected skin. Further vigilance of the vaccine side effect and investigation for the role of SP is warranted.